2021
DOI: 10.1111/famp.12661
|View full text |Cite
|
Sign up to set email alerts
|

A Longitudinal Examination of Common Dyadic Coping and Sexual Distress in New Parent Couples during the Transition to Parenthood

Abstract: New parents experience significant disruption to their sexual relationships such as lower desire and sexual frequency relative to prepregnancy. Little is known about the sexual distress new parents feel related to these changes, how sexual distress evolves over time, or how coping with stress relates to this distress. New parent couples who engage in more adaptive, joint coping with mutual stressors—common dyadic coping (CDC)—may be better able to manage distress related to their sexuality and thus, experience… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 64 publications
0
6
0
Order By: Relevance
“…Only one study to our knowledge has specifically examined dyadic coping and sexuality in new parent couples. In the study, greater common dyadic coping was associated with an individual’s own lower sexual distress—negative feelings associated with one’s sexual relationship (Derogatis et al, 2008)—at 3-months postpartum, but was not associated with how their sexual distress changed over time (Tutelman et al, 2021). These results suggest that how new parents cope together is important for managing sexual distress at a time when most couples have just resumed sexual activity and are experiencing significantly low sexual desire and satisfaction (Lurie et al, 2013; Rosen et al, 2020).…”
Section: Links Between Dyadic Coping and Sexual Desire Sexual Satisfa...mentioning
confidence: 81%
See 1 more Smart Citation
“…Only one study to our knowledge has specifically examined dyadic coping and sexuality in new parent couples. In the study, greater common dyadic coping was associated with an individual’s own lower sexual distress—negative feelings associated with one’s sexual relationship (Derogatis et al, 2008)—at 3-months postpartum, but was not associated with how their sexual distress changed over time (Tutelman et al, 2021). These results suggest that how new parents cope together is important for managing sexual distress at a time when most couples have just resumed sexual activity and are experiencing significantly low sexual desire and satisfaction (Lurie et al, 2013; Rosen et al, 2020).…”
Section: Links Between Dyadic Coping and Sexual Desire Sexual Satisfa...mentioning
confidence: 81%
“…To the best of our knowledge, with the exception of the aforementioned studies (i.e., Bodenmann et al, 2010; Rosen et al, 2017; Tutelman et al, 2021), previous cross-sectional and daily experience research has focused primarily on how couples’ dyadic coping relates to their relationship satisfaction, neglecting sexual outcomes. The only study that explored dyadic coping and sexuality in the transition to parenthood (i.e., Tutelman et al, 2021) focused on sexual distress over months, not days, and ignored positive aspects of sexual well-being (e.g., sexual desire, satisfaction) despite their importance for couple and family well-being (Brezsnyak & Whisman, 2004; Joel et al, 2020). Thus, we aimed to establish associations between dyadic coping and sexual outcomes as a first step in elucidating these relationships.…”
Section: Current Studymentioning
confidence: 99%
“…Indeed, greater dyadic coping has been associated with higher sexual satisfaction and more frequent orgasms in a sample of female students (Bodenmann et al, 2010, 2019). Two recent studies have also revealed associations between lower levels of positive and higher levels of negative dyadic coping and sexual dissatisfaction in a community sample of men and women (Wawrziczny et al, 2021) and between higher perceptions of common dyadic coping and lower sexual distress in new parent couples (Tutelman et al, 2022).…”
Section: Dyadic Copingmentioning
confidence: 97%
“…Studies following couples from pregnancy to up to one‐year postpartum have confirmed that, on average, new mothers' and partners' sexual satisfaction significantly declines. Also, mothers' sexual distress significantly increases during pregnancy and then declines at postpartum, whereas partners' sexual distress is stable over time (Rosen et al, 2020; Tutelman et al, 2021). Notably, a positive sexual relationship with one's partner might pose important benefits across this period.…”
Section: Sexual Well‐being Across the Transition To Parenthoodmentioning
confidence: 99%